(untitled) (Nigerian Journal of Pharmaceutical Research, 2021)
Background: An evaluation of the effect of Moringa oleifera methanol leaves extracts on Sodium/Potassium ATPase in streptozotocin-induced experimental diabetic albino male rats’ model. Methods: Qualitative phytochemical analysis was carried out on the methanol extracts of M. oleifera leaves using acceptable chemical methods. The LD50 of the plant extract was conducted and was non-lethal at 5000mg/kg. Thirty, albino male rats weighing 120g – 180g were arranged into five groups, comprising six rats per group. Parameters such as sodium/potassium ATPase (Na+/K+ ATPase), glycosylated hemoglobin (HbA1c), and fasting blood glucose levels were assayed. Results: M. oleifera methanol leaves extract (at 500mg/kg and 1000mg/kg) increased sodium/potassium -ATPase activities in an albino male rat induced with hyperglycemia. It was also observed that the extract at doses of 500mg/kg (132.67 + 8.14) and1000mg/kg (114.00 + 15.38) for fasting blood glucose, 500mg/kg (6.29 + 0.26) and1000mg/kg (6.08 + 0.26) for glycosylated haemoglobin (HbA1c) were effective in ameliorating diabetes induced by streptozotocin. Conclusions: This study established that the decrease in the activity of sodium/potassium -ATPase in streptozotocin-induced type II diabetes in albino male rats can be increased to normal functionality by oral administration of M. oleifera methanol leaves extracts at doses of 500mg/kg and 1000mg/kg.